Minimally invasive coronary artery bypass grafting (MINI-CABG): Protocol for a pilot randomized controlled trial comparing minimally invasive versus conventional coronary surgery - Luis Roberto Palma Dallan; Luiz Augusto Ferreira Lisboa; Luis Alberto Oliveira Dallan; Omar Asdrúbal Vilca Mejia; Antonio Francisco Neves Filho; Torsten Doenst; Oleksandr Babliak; Gustavo Alfredo Orellana Sampedro; Fabio Biscegli Jatene (PLoS ONE, 2025)
Introduction Coronary artery bypass grafting (CABG) via sternotomy remains the standard of care for multivessel coronary disease. Minimally invasive cardiac surgery for coronary artery bypass grafting (MICS-CABG) is an evolving technique with the potential to reduce surgical trauma and promote faster recovery without compromising outcomes. This protocol describes a pilot randomized controlled trial comparing MICS-CABG and conventional CABG in multivessel patients in a high-volume tertiary center. Methods and analysis This is a single-center, prospective, randomized controlled pilot trial. A total of 100 patients with multivessel coronary artery disease will be randomized (1:1) to undergo either conventional CABG via median sternotomy or MICS-CABG through a left anterior thoracotomy. The sample size of 100 patients (50 per group) was defined based on feasibility and statistical precision. This allows estimation of an expected 8% major adverse cardiovascular and cerebrovascular events (MACCE) rate with a 95% confidence interval half-width of ±5% in each group. These data will inform sample size calculations for a future phase III trial. The primary outcomes are safety and feasibility. Feasibility will be assessed by the successful completion of the planned minimally invasive coronary revascularization strategy. Safety will be evaluated through the occurrence of MACCE within 30 days postoperatively. Secondary outcomes include operative time, mechanical ventilation time, conversion rate to sternotomy, bleeding volume, atrial fibrillation, postoperative ICU and hospital length of stay, and patient-reported quality of life (EQ-5D-5L) 6 months postoperatively. The trial is ongoing at this moment. Ethics and dissemination The protocol was approved by the Institutional Research Ethics Committee under que number CAAE: 54175921.8.0000.0068. Results will be disseminated through peer-reviewed publications and scientific conferences. Trial registration number ClinicalTrials.gov NCT06794359 .